Facilities/Equipment As Panacea To Physical Education Instructional Programmes To Secondary Schools Education In Benin City, Edo State, Nigeria. - Awoma, Christopher .I.; Gabriel, Arainru (Advances in Social Sciences Research Journal, 2017)
This study examine the facilities/equipment as a panacea to physical education instructional programe in secondary schools in Benin City, Edo State, Nigeria. The study examined how facilities/equipment would be a panacea to physical education instructional programme in secondary school in Benin City, Edo State. The descriptive survey design was adopted for the study and the main research instrument used was a modified closed- ended Likert type questionnaire which was validated. The reliability of the instrument was employed using crombach alpha to determine the internal consistency of the questionnaire and 0.78% was obtained. The Data was analyzed using a combination of frequency count and simple percentages methods to describe and analyzed the data collected. The finding was that, public and approve private secondary schools in Benin City do not possess the requisite facilities/ equipment, therefore the hypothesis which says that public and private secondary schools in Benin City do not possess the requisite facilities/equipment was accepted. Based on the finding it was recommended among others that, communities, parents teacher Association and lover of sports can help to provide physical education facilities and equipment for effective teaching of physical education in both theoretical and practical. Also provision of sports equipment should be enhanced through planned annual target, while also private interested individual should be solicited and encouraged by the government.